Renal and Urinary Levels of Endothelial Protein C Receptor Correlate with Acute Renal Allograft Rejection - Lattenist, Lionel; Kers, Jesper; Claessen, Nike; ten Berge, Ineke J. M.; Bemelman, Frederike J.; Florquin, Sandrine; Roelofs, Joris J. T. H. (PloS one, 2013)
The Endothelial Protein C Receptor (EPCR) is expressed on leukocytes, on endothelium of large blood vessels and to a lesser extent on capillaries. Membrane bound EPCR plays an important role in the activation of protein C which has anticoagulant, anti-inflammatory and cytoprotective effects. After cleavage by a protease EPCR is also found as a soluble protein. Acute rejection of kidney allografts can be divided in T-cell-mediated rejection (TCMR) and antibody-mediated (ABMR) rejection. The latter is characterized by strong activation of coagulation. Currently no reliable non-invasive biomarkers are available to monitor rejection. Renal biopsies were available from 81 renal transplant patients (33 without rejection, 26 TCMR and 22 ABMR), we had access to mRNA material, matched plasma and urine samples for a portion of this cohort. Renal EPCR expression was assessed by RT-PCR and immunostaining. Plasma and urine sEPCR levels were measured by ELISA. ABMR patients showed higher levels of EPCR mRNA than TCMR patients. EPCR expression on glomeruli was significantly elevated in ABMR patients than in TCMR or control patients. In the peritubular capillaries EPCR expression was higher in ABMR patients than in control patients. EPCR expression was higher in tubules and arteries of rejection patients than in control patients. Plasma sEPCR levels did not differ. Urine sEPCR levels were more elevated in the ABMR group than in patients with TCMR or without rejection. ROC analysis demonstrated that urinary sEPCR is appropriate to discriminate between ABMR patients and TCMR or control patients. We conclude that urinary sEPCR could be a novel non-invasive biomarker of antibody mediated rejection in renal transplantation.